Global Tendency of Carbon Dioxide (CO2) per GDP as a Measure of the Environmental/Economic Risk Density - Pena-Sanchez, Rolando (European Journal of Applied Sciences, 2024)
This report contains an analysis of the global carbon dioxide (CO2) trend among the current five great titans of the world economy (United States, China, Germany, Japan, and India); and we review how these countries are contributing to the production of greenhouse gases, where we can interpret CO2 per GDP by country as a measure of environmental/economic risk density for the mentioned countries; from which some curvilinear relationships were measured through regression analysis, and homogeneous blocks with similar density were identified through a parametric analysis of variance (ANOVA) and a nonparametric statistical technique (Kruskal-Wallis test), where both methodologies generated the same conclusions.